Penaruh Penambahan Al-TiB Terhadap Kekerasan Produk Pengecoran Sentrifugal Velg Alumunium A 356 - Ali Achmadi (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2016)
One of the problem in the small industry creating velg process, is in low quality product compared tomanufactures. Current result of research concludes that the quality product small industry isinfluenced by casting method used gravity casting method. To improve its quality mechanicalproperties, casting method can be designed to sentrifugal method by adding master alloy Al-TiB. Thisresearch go in certain directionto know the influence of adding Al-TiB toward the hardness on processof sentrifugal casting, and for determine how much the percentage of Al-TlB that results the mostoptimum velg. This research conducted by using experimental method, the material used that isaluminum A 356, added Al-TiB in the amount of 0%, 0,12%, 0,17%, 0,22%, and 27%. Along with thecasting is conducted in 400 Rpm rotation. The result of study proves the change in the hardnesseffected adding variation of Al-TiB.The result of observation through the research shows that there isimpronement of mechanical properties. It is the improvement of hardness from 60,42 HRB, withadding Al-TIB in the mount of 0,12%, and if it is compared between local velg product and maufacturesproduct, so as a result, there is the improvement of the hardness score from 25,17 HRB local productand the hardness score 23,67 HRB, the manufactured product becomes 60,42 HRB by adding Al-TiB0,12%.